HAKEKAT HUKUM PIDANA TERHADAP PERBUATAN MELAWAN HUKUM DI MASYARAKAT - Farahwati Farahwati (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2015)
The law inforcement of criminal law is one of the effort to get or create the regulation, security, and peaceful in society even it’s one of the way to prevent or criminal prosecution or the violation of law. From the formal juridical aspect a crime is forms of behavior that is contrary to human morals, detrimental to society, and in violation of the law. Criminal law as a public law so everey violation of state law through the State fittings such as police, prosecutors and judges take immediate legal action.Judiciary institution has a central position as an effort to enforce laws cored justice. The principle in the investigation of criminal cases at the trial court must assume that all persons suspected, arrested, detained, charged and appear before the court or shall be deemed not guilty before a court ruling that declared his mistakes and gain permanent legal force.